Qualitative approach of Muslim entrepreneurs behavioural patterns through entrepreneurial learning competencies / Noor Malinjasari Ali, Rahayu Izwani Borhanuddin and Raslina Mohamed Nor - Ali, Noor Malinjasari; Borhanuddin, Rahayu Izwani; Mohamed Nor, Raslina (2012)
The purpose of this study is to explore the behavioural patterns of Muslim entrepreneurs through a conceptualization of entrepreneurial learning as a "competency". Semi-structured interviews to seven Muslim entrepreneurs were conducted based on a competency framework of entrepreneurial learning. The learning behaviours of Muslim entrepreneurs exhibited during theinterviews were coded and checked to see if they are in accordance with the Islamic practice. The findings suggested that there are seven behavioural patterns of entrepreneurial learning. They are actively seeking learning opportunities, learning in depth, learning continuously, learning with purpose and being selective, improving and reflecting upon experience, and successfully transferring prior experience into current practices. This behavioural learning is also parallel with the Islamic rules and regulations. The study of entrepreneurial learning under a competency framework allows us to explore the behavioural patterns and other factors that are involved ineffective entrepreneurial learning which is closely connected to entrepreneurial success without discarding the Islamic input.